Poster Development and Presentation to Improve Scientific Inquiry and Broaden Effective Scientific Communication Skills - Ines Rauschenbach (American Society for Microbiology, 2018)
We have redesigned a tried-and-true laboratory exercise into an inquiry-based team activity exploring microbial growth control, and implemented this activity as the basis for preparing a scientific poster in a large, multi-section laboratory course. Spanning most of the semester, this project culminates in a poster presentation of data generated from a student-designed experiment. Students use and apply the scientific method and improve written and verbal communication skills. The guided inquiry format of this exercise provides the opportunity for student collaboration through cooperative learning. For each learning objective, a percentage score was tabulated (learning objective score = points awarded/total possible points). A score of 80% was our benchmark for achieving each objective. At least 76% of the student groups participating in this project over two semesters achieved each learning goal. Student perceptions of the project were evaluated using a survey. Nearly 90% of participating students felt they had learned a great deal in the areas of formulating a hypothesis, experimental design, and collecting and analyzing data; 72% of students felt this project had improved their scientific writing skills. In a separate survey, 84% of students who responded felt that peer review was valuable in improving their final poster submission. We designed this inquiry-based poster project to improve student scientific communication skills. This exercise is appropriate for any microbiology laboratory course whose learning outcomes include the development of scientific inquiry and literacy.